Effect of Pruning and Fertilizers on Growth, Flowering and Yield of Cucumber (Cucumis sativus L.) under Protected Structure in Panchthar, Nepal - Chapagain, Upama; Bhandari, Sujan; Shrestha, Yogendra Man; Bista, Sagar; Dahal, Januka (International Journal of Applied Sciences and Biotechnology, 2022)
A study was conducted to determine the effect of pruning practices and different fertilizer combinations on Bhaktapur local variety of cucumber under protected structure in Panchthar, Nepal during February to June 2021. The experiment was laid out in two factorial Randomized Complete Block Design with three replications. Treatments used were two pruning practices (no pruning and 3G cutting) and four fertilizer doses (no fertilizer (control), 30 Mt/ha FYM+ 100% RDF (140:60:100 kg of NPK), 9.4 Mt/ha Vermicompost+ 100% RDF of NPK and 4.3 Mt/ha Poultry manure+ 100% RDF of NPK). Although 3G cutting practice increased the days required for 50 % flowering, it significantly decreased the male: female flowers ratio (1.69) compared to no pruning (4.38). Similarly, number of fruits per plant, individual fruit weight, fruit diameter and average fruit yield (95.21 Mt/ha) were maximum in 3G cutting. In terms of fertilizers, time requirement for 50% male flowering remained unaffected, however, plants treated with fertilizers 30 Mt/ha FYM+ 100% RDF of NPK showed significantly least days required for 50% female flowering, lowest male: female flowers ratio (2.41), maximum number of fruits per plant, maximum average individual fruit weight and highest average yield (105.78 Mt/ha) which are statistically at par with results of 9.4 Mt/ha vermicompost+ 100% RDF of NPK and 4.3 Mt/ha poultry manure+ 100% RDF of NPK for these parameters. The results concluded that combined application of organic manures and inorganic fertilizers in recommended dose with 3G pruning practices is best for growth and yield of cucumber.